化简3/4X^2Y-[1/2XY+1/2(1/2X^2-9XY)]

来源:学生作业帮助网 编辑:作业帮 时间:2017/02/28 15:39:32
XY(XY+3)+(XY+4)+4(X+Y+1)-(X+Y+2)

XY(XY+3)+(XY+4)+4(X+Y+1)-(X+Y+2)XY(XY+3)+(XY+4)+4(X+Y+1)-(X+Y+2)XY(XY+3)+(XY+4)+4(X+Y+1)-(X+Y+2)XY(X

化简!1、(x^2-xy)+xy+y^2 2、3(x^2-xy)-xy+y^2

化简!1、(x^2-xy)+xy+y^22、3(x^2-xy)-xy+y^2化简!1、(x^2-xy)+xy+y^22、3(x^2-xy)-xy+y^2化简!1、(x^2-xy)+xy+y^22、3(

化简 2(xy-xy²+3)-(-4xy²+xy-1) 其中,x等于--4,y等于-3

化简2(xy-xy²+3)-(-4xy²+xy-1)其中,x等于--4,y等于-3化简2(xy-xy²+3)-(-4xy²+xy-1)其中,x等于--4,y等于

(x+y)(x+y+2xy)+(xy+1)(xy-1)(x+y)(x-y)+4(y-1)

(x+y)(x+y+2xy)+(xy+1)(xy-1)(x+y)(x-y)+4(y-1)(x+y)(x+y+2xy)+(xy+1)(xy-1)(x+y)(x-y)+4(y-1)(x+y)(x+y+2x

若x-y=4,xy=1,求(-2xy+2x+3y)-(3xy+2y-2x)-(x+4y+xy)的值

若x-y=4,xy=1,求(-2xy+2x+3y)-(3xy+2y-2x)-(x+4y+xy)的值若x-y=4,xy=1,求(-2xy+2x+3y)-(3xy+2y-2x)-(x+4y+xy)的值若x

(-2xy+2x+5y)-(3xy+2y-2x)-(x+4y+xy)其中x-y=4xy=-1

(-2xy+2x+5y)-(3xy+2y-2x)-(x+4y+xy)其中x-y=4xy=-1(-2xy+2x+5y)-(3xy+2y-2x)-(x+4y+xy)其中x-y=4xy=-1(-2xy+2x

x-y=1,xy=2.求:(-2xy+2x+3y)-(3xy+2y-2x)-(x+4y+xy)的值

x-y=1,xy=2.求:(-2xy+2x+3y)-(3xy+2y-2x)-(x+4y+xy)的值x-y=1,xy=2.求:(-2xy+2x+3y)-(3xy+2y-2x)-(x+4y+xy)的值x-

.已知:x-y=1,xy=-2.求:(-2xy+2 x+3y)-(3xy+2y-2x)-(x+4y+xy)的值

.已知:x-y=1,xy=-2.求:(-2xy+2x+3y)-(3xy+2y-2x)-(x+4y+xy)的值.已知:x-y=1,xy=-2.求:(-2xy+2x+3y)-(3xy+2y-2x)-(x+

若x-y=4,xy=1,则(2x+y-2xy)-(3x+2y+xy)-(4xy+3y-5x)=

若x-y=4,xy=1,则(2x+y-2xy)-(3x+2y+xy)-(4xy+3y-5x)=若x-y=4,xy=1,则(2x+y-2xy)-(3x+2y+xy)-(4xy+3y-5x)=若x-y=4

化简:3x^2-[5xy-(x^y-3xy)+4x^2y-8xy]

化简:3x^2-[5xy-(x^y-3xy)+4x^2y-8xy]化简:3x^2-[5xy-(x^y-3xy)+4x^2y-8xy]化简:3x^2-[5xy-(x^y-3xy)+4x^2y-8xy]3

化简:[4xy(x-y)^-1 + (xy^-1 - x^-1y)/(x^-1 + y^-1)] / (x+y)^2

化简:[4xy(x-y)^-1+(xy^-1-x^-1y)/(x^-1+y^-1)]/(x+y)^2化简:[4xy(x-y)^-1+(xy^-1-x^-1y)/(x^-1+y^-1)]/(x+y)^2

计算3xy[2xy-x(y-2)+x-1]

计算3xy[2xy-x(y-2)+x-1]计算3xy[2xy-x(y-2)+x-1]计算3xy[2xy-x(y-2)+x-1]3xy[2xy-x(y-2)+x-1]=3xy(2xy-xy+2x+x-1

4xy-[(x²+5xy-y²)-(3xy-1/2y)]x=3,y=-6

4xy-[(x²+5xy-y²)-(3xy-1/2y)]x=3,y=-64xy-[(x²+5xy-y²)-(3xy-1/2y)]x=3,y=-64xy-[(x&

x²-y²+5x+3y+4(x+y-2xy)(x+y-z)+(xy-1)²

x²-y²+5x+3y+4(x+y-2xy)(x+y-z)+(xy-1)²x²-y²+5x+3y+4(x+y-2xy)(x+y-z)+(xy-1)&#

化简-12xy^2*1/3x^3y^4-x(2xy^2)^3

化简-12xy^2*1/3x^3y^4-x(2xy^2)^3化简-12xy^2*1/3x^3y^4-x(2xy^2)^3化简-12xy^2*1/3x^3y^4-x(2xy^2)^3-12xy^2*1/

化简-12xy^2*1/3x^3y^4-x(2xy^2)^3

化简-12xy^2*1/3x^3y^4-x(2xy^2)^3化简-12xy^2*1/3x^3y^4-x(2xy^2)^3化简-12xy^2*1/3x^3y^4-x(2xy^2)^3-12xy^2*1/

已知x y=1,xy=-3,求2xy-4x 4(y-2(xy-x))

已知xy=1,xy=-3,求2xy-4x4(y-2(xy-x))已知xy=1,xy=-3,求2xy-4x4(y-2(xy-x))已知xy=1,xy=-3,求2xy-4x4(y-2(xy-x))题目不完

4xy-[(x²+5xy-y²)-(x²+3xy-2y²)],其中x=2,y=-1求值,化简

4xy-[(x²+5xy-y²)-(x²+3xy-2y²)],其中x=2,y=-1求值,化简4xy-[(x²+5xy-y²)-(x²

xy(xy+1)+xy+3-2(x+y+1/2)-(x+y-1)^2因式分解

xy(xy+1)+xy+3-2(x+y+1/2)-(x+y-1)^2因式分解xy(xy+1)+xy+3-2(x+y+1/2)-(x+y-1)^2因式分解xy(xy+1)+xy+3-2(x+y+1/2)